Portraying the Resilience of Adolescents Thriving in Terror-Prone Conflict Zones - Mangundap, Faldi Putra; Huwae, Arthur (Kuras Institute, 2024)
Adolescence is an age that is very vulnerable in the development process because adolescents have not yet reached the cognitive and physical maturity of adolescence. At this level, teenagers are very vulnerable to experiencing setbacks, and one of them is due to the terrorist conflict they have experienced. This condition has a huge impact on the life process and mental health problems of teenagers. One of the things needed is for teenagers to become resilient, so they can recover from difficult and risky times. This research aims to examine the portrait of the resilience of teenagers living in areas prone to terrorist conflict. The method used is qualitative descriptive phenomenology. Participants involved 3 teenagers living in terrorist conflict areas who used the snowball sampling technique. The data collection process was carried out through structured interviews. The research results show that in general, resilience in adolescents living in areas prone to terrorist conflict can be achieved. Researchers also discovered a new factor influencing resilience: belief in religion, which has been the guideline for individual life.